Clinical Outcome of Subthalamic Stimulation in Parkinson's Disease is Improved by Intraoperative Multiple Trajectories Microelectrode Recording - Reck, Christiane; Maarouf, Mohammad; Wojtecki, Lars; Groiss, Stefan Jun; Florin, Esther; Sturm, Volker; Fink, Gereon R.; Schnitzler, Alfons; Timmermann, Lars (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background and Study Aims The use of multiple trajectories microelectrode recording (MER) during implantation of deep brain stimulation (DBS) electrodes into the subthalamic nucleus (STN) in patients with Parkinson's disease (PD) is discussed controversially because of possible risks and unclear benefits. The aim of the study is to investigate whether MER combined with intraoperative evaluation of stimulation effects improve clinical outcome in PD patients undergoing STN DBS surgery.Material and Methods Prior to final DBS electrode implantation, we performed multiple trajectories MER and intraoperative test stimulations after magnetic resonance imaging (MRI)-guided planning in 32 PD patients. In further 10 patients no MER (only intraoperative test stimulation) was used.Results We found a significantly better clinical outcome (Unified Parkinson's Disease Rating Scale [UPDRS] III) in patients undergoing MER compared with non-MER patients. In MER patients, DBS electrode placement was performed using the central trajectory in 73%. Another than the central trajectory was taken in 27% of the patients. No difference in clinical outcome between DBS electrodes implanted on the central or a decentral trajectory was observed.Conclusions DBS surgery based on intraoperative multiple trajectories MER and test stimulation improves clinical outcome if compared with intraoperative test stimulation alone. The data suggest that DBS surgery solely based on MRI and intraoperative test stimulation without MER may lead to nonoptimal placement of DBS electrodes and consequently poorer clinical outcome.
Keywords: deep brain stimulation; microelectrode recording; Parkinson's disease; subthalamic nucleus